A dual optical and nuclear imaging reagent for peptide labelling via disulfide bridging1. Issue 37 (7th October 2015) - Fletcher, Sally A.; Sin, Pak Kwan Brian; Nobles, Muriel; Årstad, Erik; Tinker, Andrew; Baker, James R.
<x xml:space="preserve">Abstract</x> We report a concise approach to a multimodal imaging reagent for peptide labelling via disulfide bridging. The reagent is constructed using a one pot, three component, [3 + 2] cycloaddition of a fluorescent azide with a dithiomaleimide-alkyne, with concomitant incorporation of 125I.